Alpha-synuclein Toxicity in the Early Secretory Pathway: How It Drives Neurodegeneration in Parkinsons Disease - Wang, Ting; Hay, Jesse C. (Frontiers in Neuroscience, 2015)
Alpha-synuclein is a predominant player in the pathogenesis of Parkinson's Disease. However, despite extensive study for two decades, its physiological and pathological mechanisms remain poorly understood. Alpha-synuclein forms a perplexing web of interactions with lipids, trafficking machinery, and other regulatory factors. One emerging consensus is that synaptic vesicles are likely the functional site for alpha-synuclein, where it appears to facilitate vesicle docking and fusion. On the other hand, the dysfunctions of alpha-synuclein are more dispersed and numerous; when mutated or over-expressed, alpha-synuclein affects several membrane trafficking and stress pathways, including exocytosis, ER-to-Golgi transport, ER stress, Golgi homeostasis, endocytosis, autophagy, oxidative stress, and others. Here we examine recent developments in alpha-synuclein's toxicity in the early secretory pathway placed in the context of emerging themes from other affected pathways to help illuminate its underlying pathogenic mechanisms in neurodegeneration.